2020 is the year of unknowns. Issue 8 (13th November 2020) - Zacarese, Lawrence M.
Abstract : Six months ago, I sat down to pen my quarterly column in a mental fog, struggling to keep the days of the week straight and working on little sleep. Fast forward to today and so much has transpired that it's hard to believe it has only been half a year. In the midst of a global pandemic, societal unrest, economic uncertainty, a political divide, and vitriol, we've made it. We are still here. I would say I told you so, but that is not in my nature (insert smirking emoji). Sure, things certainly don't look like they did a year ago and we have had to adjust to some of the temporary changes on our campuses, but they are just that: temporary. If you are lucky enough to have resumed some semblance of in‐person classes for this semester, as my campus has done, it looks and feels odd.